PENGARUH KAPUR TOHOR UNTUK EKSTRAKSI BENIH TERHADAP VlABILITAS BEIH MANGGIS (Garcinia mangostana L - Endang Murniati; , Rostiati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
The objectives of this experiment were to evaluate the possibility of using quick lime for extraction of mangosteen seed and the effects on its viability; The experiment was done in Seed Science and Technology Laboratory, Greenhouse, Bogor Agriculture University from November 1997 until February 1998. The materials were taken from smallholder plantation in Jasinga, Bogor. The treatments were arranged factorial in a group randomized block design with two factors. The first factor was 6 levels of quick lime concentration (K) : 0 g/l, 10 g/l, 15 g/l, 20 g/l, 25 g/l, 30 g/l and the second factor was 4 levels of soak periods: 0 minute, 10 minutes, 20 minutes, 30 minutes. The experiments had 24 treatments combination with 4 replicates so there were 72 experiment units. The data show that seed extraction using quick lime gave statistically significant different results compared with seed extraction without using quick lime and so the soak periods compared with no soak. Interaction between 20 g/l quick lime concentration and 30 minutes soak period gave the best seed emergence (96 %). 20 g/l quick lime concentration save higher vigour than other concentration as measured from its speed of germination, spontaneous growth, and root length. The soak periods increased seed moisture content 30 minutes soak period resulted higher viability and vigour than other soak periods as measured from its normal seed dry weigh, spontaneous growth, epycotyl length and root length.